Effects of forward and backward span trainings on working memory: Evidence from a randomized controlled trial. (27th July 2022) - Li, Yang; Fu, Wenjin; Zhang, Qiumei; Chen, Xiongying; Li, Xiaohong; Du, Boqi; Deng, Xiaoxiang; Ji, Feng; Dong, Qi; Jaeggi, Susanne M.; Chen, Chuansheng; Li, Jun
Abstract: Both forward and backward working memory span tasks have been used in cognitive training, but no study has been conducted to test whether the two types of trainings are equally effective. Based on data from a randomized controlled trial, this study ( N = 60 healthy college students) tested the effects of backward span training, forward span training, and no intervention. Event‐related potential (ERP) signals were recorded at the pre‐, mid‐, and post‐tests while the subjects were performing a distractor version of the change detection task, which included three conditions (2 targets and 0 distractor [2T0D]; 4 targets and 0 distractor [4T0D]; and 2 targets and 2 distractors [2T2D]). Behavioral data were collected from two additional tasks: a multi‐object version of the change detection task, and a suppress task. Compared to no intervention, both forward and backward span trainings led to significantly greater improvement in working memory maintenance, based on indices from both behavioral (Kmax) and ERP data (CDA_2T0D and CDA_4T0D). Backward span training also improved interference control based on the ERP data (CDA_filtering efficiency) to a greater extent than did forward span training and no intervention, but the three groups did not differ in terms of behavioral indices of interference control. These results have potential implications for optimizing the current cognitive training on working memory. Abstract : Both forward and backward memory span tasks have been used in cognitive training programs, but no study has explored whether their effects are the same. The current study found that both types of training may improve maintenance processes and that backward span training may also improve interference control, which suggests that adding more backward span training to the current available programs would make them more effective.